Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.4093/dmj.2011.35.2.149
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Adenosine Deaminase Activity in Patients with Type 2 Diabetes Mellitus and Effect of DPP-4 Inhibitor Treatment on ADA Activity

Abstract: BackgroundDipeptidyl peptidase 4 (DPP-4, also known as CD26) binds with adenosine deaminase (ADA) to activate T lymphocytes. Here, we investigated whether ADA activity is specifically affected by treatment with DPP-4 inhibitor (DPP4I) compared with other anti-diabetic agents.MethodsFasting ADA activity, in addition to various metabolic and biochemical parameters, were measured in 262 type 2 diabetes mellitus (T2DM) patients taking various anti-diabetic agents and in 46 non-diabetic control subjects.ResultsADA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
30
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 36 publications
2
30
0
Order By: Relevance
“…Inosine and 2'-deoxyinosine are converted to hypoxanthine, xanthine and finally to uric acid. 5,6 Highest ADA activity is observed in the lymphoid and fatty tissues, liver, skeletal muscle, and heart, although the activity is widely distributed in most organs. 7 An increase in ADA activity in T2DM patients has been reported by several researchers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inosine and 2'-deoxyinosine are converted to hypoxanthine, xanthine and finally to uric acid. 5,6 Highest ADA activity is observed in the lymphoid and fatty tissues, liver, skeletal muscle, and heart, although the activity is widely distributed in most organs. 7 An increase in ADA activity in T2DM patients has been reported by several researchers.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Elevated ADA levels are also found in obesity, metabolic syndrome, liver cirrhosis and hepatoma, TB, brucellosis, typhoid fever, hypoxic states and cell mediated immune responses. 6,10,11 However, it is difficult to conclude whether changes in ADA activity are the cause or result of actual insulin resistance. [12][13][14][15] In the present study, we measured serum ADA activity in T2DM patients to evaluate the relationship between serum ADA activity with glycemic status and various metabolic parameters in T2DM patients.…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have reported an increased serum ADA levels and also correlated with glycemic control in T2DM patients [30,31] . Moreover, higher serum ADA have also been seen in nonobese T2DM cases and correlated with fasting plasma glucose [7] .…”
Section: Discussionmentioning
confidence: 99%
“…As adenosine causes apoptosis and inhibits differentiation of T lymphocytes by activating P1 adenosine receptors, interface of ADA with DPP-4 may lead to T cell proliferation and increased cytokine production which can interfere with insulin signalling [22][23][24][25] . Cytokines stimulate the acute-phase proteins.…”
Section: Discussionmentioning
confidence: 99%
“…However, less information is available regarding cardio-protective effects of the DPP4 inhibitors. In addition to preventing the deactivation of endogenous GLP-1, DPP4 inhibitors also have anti-inflammatory properties and can bind adenosine deaminase, thereby elevating extracellular adenosine levels [9].…”
mentioning
confidence: 99%